Together But Different: The Subgenomes of the Bimodal Eleutherine Karyotypes Are Differentially Organized - Báez, Mariana; Vaio, Magdalena; Dreissig, Steven; Schubert, Veit; Houben, Andreas; Pedrosa-Harand, Andrea (Frontiers in Plant Science, 2019)
Bimodal karyotypes are characterized by the presence of two sets of chromosomes of contrasting size. Eleutherine bulbosa (2n = 12) presents a bimodal karyotype with a large chromosome pair, which has a pericentric inversion in permanent heterozygosity with suppressed recombination, and five pairs of 3-4 times smaller chromosomes. Aiming to understand whether high copy number sequence composition differs between both chromosome sets, we investigated the repetitive DNA fraction of E. bulbosa and compared it to the chromosomal organization of the related E. latifolia species, not containing the pericentric inversion. We also compared the repetitive sequence proportions between the heteromorphic large chromosomes of E. bulbosa and between E. bulbosa and E. latifolia to understand the influence of the chromosome inversion on the dynamics of repetitive sequences. The most abundant repetitive families of the genome showed a similar chromosomal distribution in both homologues of the large pair and in both species, apparently not influenced by the species-specific inversions. The repeat families Ebusat1 and Ebusat4 are localized interstitially only on the large chromosome pair, while Ebusat2 is located in the centromeric region of all chromosomes. The four most abundant retrotransposon lineages are accumulated in the large chromosome pair. Replication timing and distribution of epigenetic and transcriptional marks differ between large and small chromosomes. The differential distribution of retroelements appears to be related to the bimodal condition and is not influenced by the nonrecombining chromosome inversions in these species. Thus, the large and small chromosome subgenomes of the bimodal Eleutherine karyotype are differentially organized and provably evolved by repetitive sequences accumulation on the large chromosome set.